Computer-Based Tools Unmask Critical Mineral Nutrient Interactions in Hoagland Solution for Healthy Kiwiberry Plant Acclimatization - Maleki, Sara; Maleki Zanjani, Bahram; Kohnehrouz, Bahram Baghban; Landin, Mariana; Gallego, Pedro Pablo (Frontiers in Plant Science, 2021)
The aim of this study was to better understand the response of ex vitro acclimatized plants grown to a set of mineral nutrient combinations based on Hoagland solution. To reach that, two computer-based tools were used: design of experiments (DOE) and a hybrid Artificial Intelligence technology that combines artificial neural networks with fuzzy logic. DOE was employed to create a five-dimensional IV-design space by categorizing all macroelements and one microelement (copper) of Hoagland mineral solution, reducing the experimental design space from 243 (35) to 19 treatments. Typical growth parameters including hardening efficiency (Hard), newly formed shoot length (SL), total leaf number (TLN), leaf chlorophyll content (LCC), and leaf area (LA). And three physiological disorders: leaf necrosis (LN), leaf spot (LS), and curled leaf (CL) were evaluated for each treatment (mineral formulation). All the growth parameters plus LN were successfully modeled using neurofuzzy logic with a high Train Set R2 between experimental and predicted values (72.67 < R2 < 98.79). The model deciphered new insights, by different sets of ‘IF–THEN’ rules, pinpointing the positive role of Mg2+ and Ca2+ to improve Hard, SL, TLN, and LA, and alleviate LN but with their opposite influences on LCC. On the other hand, TLN and LCC were negatively affected by the addition of NO3- into the media. Whilst NH4+ in complex interaction with Cu2+ or Mg2+ positively enhanced SL, TLN, LCC, and LA. In our opinion, the approach and results achieved in this work are extremely fruitful to understand the effect of Hoagland mineral nutrients on the healthy growth of ex vitro acclimatized plants, through identifying key factors favoring growth and limiting physiological abnormalities.